The Value of Left Anterior Mediastinotomy For Staging Left Upper Lobe Non-Small Cell Lung Cancer - Koşar, Altuğ; Örki, Alpay; Kıral, Hakan; Temürtürkan, Kemal; Eryiğit, Hatice; Şenol, Canan Dudu (Fırat University, 2005)
Objectives: Anterior mediastinotomy was commonly used for the evaluation of anterior mediastinal lymph nodes, mediastinum, pulmonary hilum and parenchym. Materials and Methods: Left anterior mediastinotomy (LAM) was performed for the staging of left upper lobe non-small cell lung carcinoma (NSCLC) in 76 cases between 1995 and 2004 years. There were 70 male, 6 female with the median age 53.4 (23-73). Nineteen of those cases were underwent intrapericardial exploration (IPE) to evaluate the resectability. Results: One or more than one (n=61) mediastinal tissue invasion were detected in 45 cases. Thirty-one cases, which were considered as an operable group after LAM, underwent standard cervical mediastinoscopy (SCM). Thoracotomy was performed to 26 cases, because of the detection of metastatic lymph nodes in 5 cases after SCM. Resection could not be performed because of perioperative cardiac problems in 3 and decendan aort invasion in 2 of the cases. Complete resection was achieved all the 21 cases except one. No mortality was detected. Complications were, developed local tumor recurrence on the incision scar 13 months after LAM (n=1), temporary hoarseness (n=2) and wound infection (n=2). According to our results, LAM had 100% specifity and 95.7% sensitivity. Conclusion: LAM should be performed in the staging of left upper lobe NSCLC with SCM. The reliability of the LAM and IPE is more than 90% in order to decide the resectability. Unnecessary thoracotomies can be minimize by the method. This method can be used securely in experienced hands with low complication. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Anterior mediyastinotomi günümüzde anterior mediyastinal lenf nodlarının, mediyastinumun, pulmoner hilusun ve parankimin değerlendirilmesinde etkin bir şekilde kullanılmaktadır. Gereç ve Yöntem: 1995-2004 yılları arasında sol üst lob yerleşimli küçük hücreli dışı akciğer kanseri tanısı konulan 76 olguya evreleme amacı ile sol anterior mediyastinotomi (SAM) yapıldı. Olguların 70'i erkek, 6'sı kadın ve yaş ortalaması 53.4 (25-73) idi. Olguların 19'una rezektabiliteyi değerlendirmek amacı ile ilave olarak intraperikardiyal eksplorasyon yapıldı. Bulgular: SAM neticesinde 45 (%59.2) olguda bir veya birden fazla mediyastinal yapıda (n=61) invazyon tesbit edildi. Bu yapılar; mediyastinal plevra ve yağlı doku (n=18), 5 ve 6 no.lu lenf nodları (n=16), pulmoner arter (n=11), perikard (n=8), aort (n=7) ve inferior pulmoner ven (n=1) idi. Sol anterior mediyastinotomi sonucu operabl kabul edilen 31 olguya aynı seansta standart servikal mediyastinoskopi (SSM) yapıldı ve 5 olguda metastatik lenf nodu bulunduğu için 26 olguya torakotomi uygulandı. Torakotomi yapılan 3 olguda perioperatif dönemde kardiyak problemler gelişmesi, 2 olguda desenden aorta invazyonu nedeni ile rezeksiyon yapılamadı. Rezeksiyon yapılan 21 olgunun 1'i dışında hepsine komplet rezeksiyon yapıldı. Mortalite görülmedi. Komplikasyon olarak, SAM'den 13 ay sonra tümör ekilimine bağlı insizyon yerinde tümör (n=1), geçici ses kısıklığı (n=2) ve yara yeri enfeksiyonu (n=2) saptandı. Sol anterior mediyastinotominin spesifitesi %100, sensivitesi %95.7 olarak bulundu. Sonuç: Sol anterior mediyastinotomi; küçük hücreli dışı sol üst lob tümörlerinin evrelendirilmesinde standart servikal mediyastinoskopi ile birlikte kullanılmalıdır. SAM ve intraperikardiyak eksplorasyonun rezektabilite tayinindeki güvenilirliği % 90'ın üzerindedir. Bu sayede gereksiz torakotomiler önlenebilir. Bu yöntem deneyimli ellerde güvenle uygulanabilir ve komplikasyon oranları düşüktür. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Sol Üst Lob Küçük Hücreli Dışı Akciğer Kanserinin Evrelendirmesinde Sol Anterior Mediyastinotominin Değeri